2008
DOI: 10.1007/bf03179444
|View full text |Cite
|
Sign up to set email alerts
|

Screening of plant growth promoting traits ofBacillus thuringiensis

Abstract: -This study aimed to evaluate the plant growth promoting (PGP) potential of Bacillus thuringiensis. In this context, several genetic determinants of factors implicated in PGP potential were investigated by polymerase chain reaction (PCR) in 16 B. thuringiensis strains of different origin and belonging to different subspecies. PCR screening was performed on acid phosphatase, phytase, siderophore biosynthesis protein, 1-aminocyclopropane-1-carboxylate (ACC) deaminase and indolpyruvate decarboxylase (ipdC). Produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 42 publications
(40 reference statements)
2
44
0
7
Order By: Relevance
“…In the present study, we detected different bioactive and inactive GAs in the CF of M1021, and these results are strongly supported by earlier reports suggesting that entomopathogenic bacteria produce plant hormones. Raddadi et al (2008) have reported that several strains of Bacillus thuringiensis produce various growth-promoting metabolites including phytohormones. Similarly, Ullah et al (2013) have reported that P. temperata produces plant growth hormones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we detected different bioactive and inactive GAs in the CF of M1021, and these results are strongly supported by earlier reports suggesting that entomopathogenic bacteria produce plant hormones. Raddadi et al (2008) have reported that several strains of Bacillus thuringiensis produce various growth-promoting metabolites including phytohormones. Similarly, Ullah et al (2013) have reported that P. temperata produces plant growth hormones.…”
Section: Resultsmentioning
confidence: 99%
“…(Goswami et al 2013) have been successfully analyzed for the GAs production. Entomopathogenic bacteria have been recently reported to produce plant growth regulators (Raddadi et al 2008), that not only improve plant growth and development but also enhance the fitness of the host against a diverse array of environmental stresses Kang et al 2012). Bacteria produce GAs in culture extract that can be detected using gas chromatography coupled with mass spectrometry (GC/ MS) with selected ion monitoring mode (SIM), which has been used extensively for the analysis of metabolites because of its greater separation efficiency that resolves very complex biological mixtures (Schneider et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The gene encoding for 1-aminocyclopropane-1-carboxylic acid deaminase is ~800bp (Raddadi, Cherif, Boudabous & Daffonchio, 2008). The primers used were forward 5'-GTGAAC-CACCTGAATGTA-3' and reverse 5'-AAAC-GAGATGATTTACTTGG-3'.…”
Section: Pcr Screening For Acc Genementioning
confidence: 99%
“…Pseudomonas fluorescens group (Ga_1, Oa_2, D_6), P. vagans (D_10) and P. stutzeri (O_16) produced moderate to low quantities of IAA. Other authors reported varying levels of IAA production for different endophytic strains: 18.8 μg ml -1 for P. stutzeri, isolated from Echinacea (Lata et al, 2006), 6-13.3 μg ml -1 for Methylobacterium, isolated from clover, 0.6-45.5 μg ml -1 for endophytes from Sedum alfredii and 1.1-154 μg ml -1 for endophytes from Solanum nigrum (Raddadi et al, 2008).…”
Section: Resultsmentioning
confidence: 99%